Automotive body in white framing systems review - Mohamad Zamri Md Zain; Ahmad Majdi Abdul-Rani; Md Al-Amin; S F Khan; Muhammad Al’Hapis Abdul Razak; M.H Sulaiman; Unune, Deepak Rajendra (Penerbit Universiti Kebangsaan Malaysia, 2021)
One of the main assembly processes in Body Shop produce BIW (Body in White). Automated framing system is used to assemble main sub assembly of body parts to become a BIW. Among the challenges using BIW framing are high investment, change of model or product life cycle and multiple or mixed model in a single line.This paper conducts a systematic review on BIW framing systems for automotive scope. Study and compare on the framing systems used have been carried out. Some examples of different BIW framing systems are shown. The current trend indicates that the framing systems changed from dedicated model to multiple models which seek flexibility approach to add in. Major or big automotive OEM's have their own design of BIW framing system.